2008
DOI: 10.1001/archsurg.2007.55
|View full text |Cite
|
Sign up to set email alerts
|

Hypoparathyroidism After Total Thyroidectomy

Abstract: Patients with iPTH levels of 15 pg/mL or less and sCa levels of 1.9 mmol/L or less are at increased risk of developing postoperative hypoparathyroidism. Measuring iPTH levels 24 hours after total thyroidectomy in combination with sCa levels on the second postoperative day allows the prediction of hypoparathyroidism with a high sensitivity, specificity, and positive predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
219
2
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(260 citation statements)
references
References 26 publications
22
219
2
17
Order By: Relevance
“…Therefore, on the first 2 postoperative days, interpretation of iPTH levels in combination with sCa levels seems an optimal strategy for predicting patients at risk of hypoparathyroidism. 14 The overall incidence of transient and permanent hypoparathyroidism was 7.3% and 1.5%, respectively in a study by Thomusch O et al 15 Filho GJ demonstrated that there was transient hypocalcemia in 27.5%, permanent hypocalcemia in 5.1%. 16 Ozbas S et al in his study showed that after subtotal thyroidectomy 8.2% developed transient hypocalcaemia and 2.4% and 0.6% patients developed transient and permanent RLN palsy respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, on the first 2 postoperative days, interpretation of iPTH levels in combination with sCa levels seems an optimal strategy for predicting patients at risk of hypoparathyroidism. 14 The overall incidence of transient and permanent hypoparathyroidism was 7.3% and 1.5%, respectively in a study by Thomusch O et al 15 Filho GJ demonstrated that there was transient hypocalcemia in 27.5%, permanent hypocalcemia in 5.1%. 16 Ozbas S et al in his study showed that after subtotal thyroidectomy 8.2% developed transient hypocalcaemia and 2.4% and 0.6% patients developed transient and permanent RLN palsy respectively.…”
Section: Resultsmentioning
confidence: 96%
“…First of all, the definition of hypocalcemic symptom is subjective and arbitrary, and many previous studies have used their own definitions (13,(24)(25)(26)(27)(28)(29). The result of this study may be biased by the threshold for pain or tingling sensation of the patients.…”
Section: Discussionmentioning
confidence: 98%
“…Laboratory tests including perioperative PTH level, total calcium, ionized calcium, and phosphorus level were evaluated (3,(9)(10)(11)(12)(13)(14)(15)(16). In most of these studies, postoperative serum PTH was recommended as the most powerful predictor for post-thyroidectomy hypocalcemia, with a sensitivity ranging from 64% to 100% and a specificity ranging from 72% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…We used this value as a cut-off point for calculating sensitivity a predictive values of iPTH in predicting postoperative hypocalcemia. This value is often used in many studies (17,18,19). Some authors in their studies looked for other values of iPTH as a cut-off point to obtain better sensitivity, or specifi city or PPV/NPV: 13 pg/ml (20), 12 pg/ml (21,22).…”
Section: Methodsmentioning
confidence: 99%